Characterization of the targeting signal in mitochondrial β-barrel proteins - Tobias Jores (Nature Portfolio, 2016)
Mitochondrial β-barrel proteins are synthesized in the cytosol before being targeted to the organelle. Here, Jores et al.show that a specialized hydrophobic β-hairpin motif is the previously undefined targeting sequence and is recognized by the mitochondrial outer membrane translocase.